Chromosome 22q a frequent site of allele loss in head and neck carcinoma - Poli-Frederico, Regina C. [UNESP]; Bergamo, Nadia A. [UNESP]; Reis, Patricia P. [UNESP]; Kowalski, Luiz P.; Zielenska, Maria; Squire, Jeremy A.; Rogatto, Silvia R. [UNESP] (My University, 2000)
Background. Loss of heterozygosity (LOH) correlates with inactivated tumor suppressor genes. LOH at chromosome arm 22q has been found in a variety of human neoplasms, suggesting that this region contains a tumor suppressor gene(s) other than NF2 important to tumorigenesis. The aim of this study was to evaluate the presence of LOH on chromosome 22q11.2-13 and determine whether there was a relationship between loss in this genomic region and tumor histologic parameters, anatomic site, and survival in patients with squamous cell carcinoma of the head and neck (HNSCC). Methods. Fifty matched blood and HNSCC tumor samples taken at the time of surgical treatment were evaluated for LOH by use of four microsatellite markers mapping to 22q11.2-q13. Clinical information was available for all patients. The frequency and distribution of LOH was correlated with clinical (age, sex, use of tobacco and alcohol, site of primary tumor, clinical stage, adjuvant therapy and overall survival) and histologic parameters (his-topathologic stage, tumor differentiation). Results. LOH at 22q was found in 19 of 50 (38%) informative tumors. The respective incidence of allelic loss for the patients was as follows: 28% at D22S421, 10% at D22S277, 8% at D22S446, and 4% at D22S280. No statistical differences were apparent with a mean follow-up of 30 months. Laryngeal tumors showed a higher incidence of LOH compared with oral tumors. Conclusions. These results suggest that the D22S277 locus may be closely linked to a tumor suppressor gene (TSG) and involved in upper aerodigestive tract carcinogenesis. In particular, laryngeal tumors may harbor another putative TSG on 22q11.2-q12.3 that may play a role in aggressive stage III/IV disease. (C) 2000 John Wiley and Sons, Inc.
Keywords: Chromosome 22; Head and neck carcinomas; Loss of heterozygosity; Microsatellites